Intra-regional tax competition and economic geography - Ossip Hühnerbein; Tobias Seidel (Center for Economic Studies and ifo Institute (CESifo), 2007)
We extent a solvable version of the core-periphery agglomeration model to four countries located in two regions. The paper shows that there might still be a race to the bottom in capital income tax rates despite agglomeration rents earned by the mobile factor. We find that intra-regional tax competition is detrimental from a welfare perspective and that tax harmonisation unambiguously makes both countries in the core region better off.
Keywords: F12; H87; 330; tax competition; economic geography; race to the bottom; Steuerwettbewerb; Kapitalertragsteuer; Kern-Peripherie-Beziehung; Neue ökonomische Geographie; Wohlfahrtseffekt; Steuerharmonisierung; Theorie